Effects of cannabidiol in the treatment of patients with Parkinson's disease: an exploratory double-blind trial - Chagas, Marcos Hortes N; Zuardi, Antonio W; Tumas, Vitor; Pena-Pereira, Márcio Alexandre; Sobreira, Emmanuelle T; Bergamaschi, Mateus M; dos Santos, Antonio Carlos; Teixeira, Antonio Lucio; Hallak, Jaime E C; Crippa, José Alexandre S (Journal of psychopharmacology (Oxford), 2014)
Parkinson's disease (PD) has a progressive course and is characterized by the degeneration of dopaminergic neurons. Although no neuroprotective treatments for PD have been found to date, the endocannabinoid system has emerged as a promising target. From a sample of 119 patients consecutively evaluated in a specialized movement disorders outpatient clinic, we selected 21 PD patients without dementia or comorbid psychiatric conditions. Participants were assigned to three groups of seven subjects each who were treated with placebo, cannabidiol (CBD) 75 mg/day or CBD 300 mg/day. One week before the trial and in the last week of treatment participants were assessed in respect to (i) motor and general symptoms score (UPDRS); (ii) well-being and quality of life (PDQ-39); and (iii) possible neuroprotective effects (BDNF and H(1)-MRS). We found no statistically significant differences in UPDRS scores, plasma BDNF levels or H(1)-MRS measures. However, the groups treated with placebo and CBD 300 mg/day had significantly different mean total scores in the PDQ-39 (p = 0.05). Our findings point to a possible effect of CBD in improving quality of life measures in PD patients with no psychiatric comorbidities; however, studies with larger samples and specific objectives are required before definitive conclusions can be drawn.